Asteroids : how love, fear, and greed will determine our future in space - Elvis, Martin (Yale University Press, 2021)
Human travel into space is an enormously expensive and unforgiving endeavor. So why go? In this accessible and authoritative book, astrophysicist Martin Elvis argues that the answer is the asteroid exploration, for motives of love, fear, and greed. Elvis's personal motivation is one of scientific love - asteroid investigations may teach us about the composition of the solar system and the origins of life. A more compelling reason may be fear - of a large asteroid hitting our planet. Finally, Elvis maintains, we should consider greed: asteroids likely hold vast riches, such as large platinum deposits, and mining them could provide both a new industry and a funding source for bolder space exploration. Elvis explains how each motive can be satisfied, and how they help one another. From the origins of life, to "space billiards" and space sports, Elvis looks at how asteroids may be used in the not-so-distant future.